Statistics between winning and losing teams by competition levels in volleyball - World Cup and Championship 2007 - Joao, P.; Mota, M.; Mesquita, I.; Sampaio, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction Game analysis (GA) allows for the interpretation of the organization of teams and the identification of game statistics so as to improve competitive performance. Volleyball game-related statistics are used to identify and control team and individual performances, aiming to find a way to score two more points than the opposing team. The characteristics identified in the diverse competition levels might present specificities for each game level. Therefore, the purpose of the present study has been to identify the game-related statistics that allow for the discrimination between winning and losing teams in competition levels in volleyball. Methods The statistics of all the games (n=344) of the diverse World championships 2007 (including all levels of competition and both genders) were analyzed using the Software VIS of the `score box` of the International Volleyball Federation (FIVB) by undertaking the analysis of the discriminating function (DF) so as to identify the indicators that contributed more to establish the maximum difference between victories and defeats. Through the structural coefficients (SC), we have identified the game-related statistics that best discriminate the levels. Results Our results showed that the obtained functions in this discriminating analysis were all statistically significant (p<0.05) and classified correctly in 82.3% of the cases. As there are high values of quality reception and excellent sets in the senior teams, they obtained lower values in the continuity reception and faults sets. At the same time, the junior teams presented higher values of continuity reception. Thus presenting a possible explanation for the occurrence of faults sets, seeing as they are two actions preceded by the opponent`s service. The structure coefficients identified team continuity reception (SC=-0.35) and faults sets (SC=-0.30) for function 1. For function 2, only the excellent digs (SC=0.32) contributed to discriminate the groups. Discussion The results are going to suggest that the greater the experience with reference to age and competition level of the players, the better the levels of reception. Contrarily, the lower the age of the players and the competition level is, the lower the number of continuity receptions. A possible explanation for these divergences in the values found in the present study may result from the differences in the tactical-technical capacity between competition levels, resulting from the differentiated qualities in the reception between extreme levels. The ensuing results of the seniors present higher values in excellent distribution, slightly lesser in relation to the following variables; the same takes place for the continuity sets and the faults sets. These profiles may better help coaches in their preparation according to this specificity, allowing teams to be ready to control these variables in competitions.